Guidelines for dental care provision during the COVID-19 pandemic - Ali Alharbi; Saad Alharbi; Shahad Alqaidi (Elsevier, 2020)
Since the coronavirus disease 2019 (COVID-19) outbreak was declared a pandemic on 11 March 2020. Several dental care facilities in affected countries have been completely closed or have been only providing minimal treatment for emergency cases. However, several facilities in some affected countries are still providing regular dental treatment. This can in part be a result of the lack of universal protocol or guidelines regulating the dental care provision during such a pandemic. This lack of guidelines can on one hand increase the nosocomial COVID-19 spread through dental health care facilities, and on the other hand deprive patients' in need of the required urgent dental care. Moreover, ceasing dental care provision during such a period will incense the burden on hospitals emergency departments already struggle with the pandemic.This work aimed to develop guidelines for dental patients' management during and after the COVID-19 pandemic.Guidelines for dental care provision during the COVID-19 pandemic were developed after considering the nature of COVID-19 pandemic, and were based on grouping the patients according to condition and need, and considering the procedures according to risk and benefit.It is hoped that the guidelines proposed in this work will help in the management of dental care around the world during and after this COVID-19 pandemic.